119 ENHANCING THE QUALITY OF STROKE CARE IN IRELAND - DEVELOPMENT OF AN IRISH NATIONAL STROKE AUDIT. (25th October 2022) - Moran, CN; Jeffares, I; Merriman, NA; McCormack, J; Harbison, J; Sexton, E; Williams, D; Kelly, PJ; Horgan, F; Collins, R; Bhreacáin, M Ní; Byrne, E; et al.
Abstract: Background: Population ageing, stroke treatment advances, changing models of care, and between-hospital heterogeneity in stroke outcomes demonstrate the necessity of continual audit of stroke care to support quality improvement at local and national levels, and to enhance patient recovery and wellbeing. This project aims to identify the core minimum datasets for acute and non-acute stroke care, and Patient-Reported Outcome Measures (PROMs), for integration in to the newly-developed Irish National Audit of Stroke (INAS), in addition to identifying resourcing needs and implementation procedures. Methods: In Phase 1, a minimum dataset for acute stroke care was identified based on a scoping review of international practice and available guidelines. Phase 2 (ongoing) involves identifying datasets for non-acute rehabilitative and follow-up care based on a scoping review of international practice, iterative cycles of qualitative stakeholder engagement, and systematic review of PROMs. In Phase 3, a review of resourcing and data collection procedures used in stroke audits internationally will be used to produce an implementation strategy for data collection, contextualised to the Irish healthcare system. Results: Twenty-one eligible international stroke registries were identified from the scoping review. Within Phase 1, core clinical and thrombectomy items in the Irish registry were benchmarked against internationally-collected items to identify common items and to generate an inventory of items that other registries collect that Ireland does not. Based on consensus agreement on the most frequently-occurring international items, as reviewed by key stakeholders, a core minimum dataset for audit of acute stroke care was delivered. Conclusion: These minimum datasets shall act as the "gold standard" for evaluating stroke care in Ireland, by not only incorporating structure, process, and care quality outcome indicators, but also PROMs. The resultant datasets may inform policy and quality improvement initiatives, and shape health service delivery across the trajectory of stroke care, from hyper-acute care, to rehabilitation, and return to the community.